Role of systemic treatment in gastric cancer - Ferrari, Natalia (2021)
Gastric cancer can be cured surgically when found in early stages, but it is still a deadly disease in many cases, especially when found in more advanced stages. Systemic and regional treatments have been added to surgery to improve the outcomes in localized disease. Systemic treatments are also used in advanced or metastatic disease to improve survival y palliate symptoms. Cytotoxic therapy, immunotherapy, monoclonal antibodies, other targeted therapies, and combinations of these have improved the survival in the metastatic setting.